The issue of sanitation in rural space: an environmental approach in three rural locations in the municipality of Nova Palma, RS - Vieira, Laciane Romero; Vieira, Licielo Romero; Vestena, Silvane (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The generation of waste can be considered an environmental issue because it is related to public health, since it is part of sanitation with water treatment and sewage has implications for the preservation and / or conservation of natural resources, especially in regard to water sources. This paper aims to conduct a survey on environmental issues of 65 families of three rural localities in the municipality of Nova Palma, RS (Bom Retiro, Linha Um and Rincão Santo Antonio) covering the use of pesticides and sanitation including relevant issues water, waste and sewage generated. For that reason, an exploratory and descriptive study was carried out using a structured questionnaire filled out by the person responsible for the family and based on environmental conditions: the existence of collection and / or destination of residential waste, the selective collection system, sewage disposal, source and treatment water consumption, the use and destination of agrochemical container on their properties from 65 families. After performing the study it was found that the majority of dwellings in the three localities studied obtains water from nascents on the farm and in most cases without treatment, except for some dwelling that reported the use of filtration and / or chlorination; the residue of the three locations is not collected, being burned or buried in large, practical regarded by the respondents, a more acceptable technique when compared to decomposing outdoor. In addition, there is a notorious awareness by owners of the three rural locations about the destination of pesticide containers used in the production of Nicotiana tabacum (tobacco), and that they are returned by farmers to tobacco companies and / or companies for cooperative farmers location. Therefore, it is noticed that an awareness program of the residents of three rural localities emphasizing how to properly manage the waste from their homes is necessary, besides seeking alternatives to reuses them as a way to decrease the volume and prevent or lessen contamination, including the proper handling and disposal of agrochemical containers.